Comorbidities and Risk Factors Associated With Insomnia in the Elderly Population - Neil Mookerjee; Nicole Schmalbach; Gianna Antinori; Subhadra Thampi; Dylan Windle-Puente; Amy Gilligan; Ha Huy; Megha Andrews; Angela Sun; Roshni Gandhi; William Benedict; Austin Chang; et al. (SAGE Publishing, 2023)
Introduction/Objectives: Sleep disorders affect around 50 to 70 million Americans, with chronic insomnia being the most common, especially in the elderly population. With an 11-fold increase in the US office visits due to insomnia, from 0.8 to 9.4 million, between 1993 and 2015, it is imperative to identify the modifiable risk factors. The aim of our study was to examine the association of risk factors and comorbid medical conditions with insomnia in patients 65 years, and older. Methods: We performed a retrospective electronic medical record review of the patients aged 65 years and older, who visited our suburban internal medicine office between July 1, 2020 and June 30, 2021. Patients were divided into insomnia group, and the group without insomnia. The associated variables were compared. Results: Among 2431 patients, 247 patients (10.2%) had insomnia. Mean ages of the patients in the insomnia group and the group without insomnia were comparable (77 ± 8.1 year vs 76 ± 7.5 year; P  = .211). There was a significantly greater frequency of women in the insomnia group compared to the group without insomnia (63.2% vs 55.5%; P  = .022). In the insomnia group, there were significantly higher frequencies of association of certain comorbidities compared to the group without insomnia, such as dementia (6.5% vs 3.4%; P  = .015), depression (30.8% vs 14.9%; P  < 0.001), anxiety disorder (34.4% vs 17.4%; P  < .001), atrial fibrillation (19.4% vs 13.4%; P  = .01), and chronic pain disorders (32.8% vs 18.9%; P  < .001). Logistic regression analysis showed significantly greater odds of insomnia in patients who had depression (OR = 1.860, 95% CI 1.342-2.576; P  < .001), anxiety (OR = 1.845, 95% CI 1.342-2.537; P  < .001), and chronic pain disorders (OR = 1.901, 95% CI 1.417-2.549; P  < .001). Conclusions: Female sex, dementia, depression, anxiety, chronic pain disorders, and atrial fibrillation are associated with insomnia in the elderly patients. Presence of depression, anxiety, and chronic pain disorders are associated with greater odds of having insomnia in the elderly patients.